2002
DOI: 10.1023/a:1015700415808
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The results are consistent with the hypothesis that consumption of alcoholic beverages increases the risk of colorectal cancer. The evidence is strongest for effects on the distal colon and rectum, and, among the three types of beverage, it most strongly implicates beer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A pooled analysis of five Japanese cohort studies also suggested positive associations between alcohol intake and risk of colon and rectal cancers in both men and women [8]. The association was more prominent for rectal cancer in some studies [32], [33], but not in other studies [34], [35], [36]. In the Health Professionals Follow-Up Study and the Nurses' Health Study, alcohol intake was associated with increased risk for colon cancer only in men, whereas no apparent associations were found between colon or rectal cancers and alcohol intake in women [36].…”
Section: Discussionmentioning
confidence: 97%
“…A pooled analysis of five Japanese cohort studies also suggested positive associations between alcohol intake and risk of colon and rectal cancers in both men and women [8]. The association was more prominent for rectal cancer in some studies [32], [33], but not in other studies [34], [35], [36]. In the Health Professionals Follow-Up Study and the Nurses' Health Study, alcohol intake was associated with increased risk for colon cancer only in men, whereas no apparent associations were found between colon or rectal cancers and alcohol intake in women [36].…”
Section: Discussionmentioning
confidence: 97%
“…1214, 32, 33 In a study of 41,837 post-menopausal women in the US, wine consumption was found to be inversely associated with distal colon cancer: RR 0.64 (95% CI 0.40, 0.98). 14 A Danish cohort study found that wine consumption lowered the risk of rectal cancer, even in combination with other alcoholic beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Of the included studies, 31 ( 31–61 ) were cohort studies, and 42 ( 62–103 ) were case–control studies. The studies were conducted in 19 different countries: the USA (30) ( 31 , 34 , 36 , 38–41 , 43 , 45 , 48 , 49 , 53 , 55 , 56 , 58 , 59 , 62 , 63 , 67 , 68 , 75 , 76 , 78 , 81 , 82 , 92 , 94 , 98 , 99 , 102 ), New Zealand (1) ( 71 ), Australia (8) ( 51 , 57 , 64 , 70 , 73 , 80 , 93 , 101 ), Canada (8) ( 37 , 60 , 70 , 74 , 86 , 89 , 97 , 103 ), Greece (2) ( 50 , 70 ), Argentina (1) ( 70 ), Uruguay (2) ( 79 , 85 ), Italy (11) ( 50 , 65 , 66 , 69 , 70 , 72 , 77 , 84 , 87 , 88 , 96 ), Netherlands (6) ( 32 , 35 , 44 ,…”
Section: Resultsmentioning
confidence: 99%
“…The total score of the included studies ranged from six to eight stars. In the selection category, one study scored two stars ( 66 ), nine studies scored three stars ( 69 , 70 , 72 , 84 , 85 , 88 , 89 , 96 , 103 ), and the remaining studies scored the maximum ( 62–65 , 67 , 68 , 71 , 73–83 , 86 , 87 , 90–95 , 97 , 102 ). In the comparability category, all studies scored the highest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation